Interpolymer radical coupling: A toolbox complementary to controlled radical polymerization - Debuigne, Antoine; Hurtgen, Marie; Detrembleur, Christophe; Jérôme, Christine; Barner-Kowollik, Christopher; Junkers, Tanja (Progress in polymer science, 2012)
The current review focuses on the relevance and practical benefit of interpolymer radical coupling methods. The latter are developing rapidly and constitute a perfectly complementary macromolecular engineering toolbox to the controlled radical polymerization techniques (CRP). Indeed, all structures formed by CRP are likely to be prone to radical coupling reactions, which multiply the available synthetic possibilities. Basically, the coupling systems can be divided in two main categories. The first one, including the atom transfer radical coupling (ATRC), silane radical atom abstraction (SRAA) and cobalt-mediated radical coupling (CMRC), relies on the recombination of macroradicals produced from a dormant species. The second one, including atom transfer nitroxide radical coupling (ATNRC), single electron transfer nitroxide radical coupling (SETNRC), enhanced spin capturing polymerization (ESCP) and nitrone/nitroso mediated radical coupling (NMRC), makes use of a radical scavenger in order to promote the conjugation of the polymer chains. More than a compilation of macromolecular engineering achievements, the present review additionally aims to emphasize the particularities, synthetic potential and present limitations of each system.